2019
DOI: 10.3390/su11102793
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Among Factors Influencing Product Innovation and Innovation Behaviour: Market Orientation, Managerial Ties, and Government Support

Abstract: Ongoing globalization and changing customer needs make it increasingly difficult for firms to survive in the long term. Innovation is considered an important tool for firms in this environment. In particular, a firm’s ability to cultivate innovative behaviour and implement product innovation for sustainability is important. This study explores resources and capabilities to enhance firm innovation behaviour and implementation of sustainable product innovation. The results provide insights on how firms can manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 106 publications
(139 reference statements)
7
33
0
2
Order By: Relevance
“…Third, there is evidence for a positive correlation between subjective performance assessments and other objective measures that use accounting or financial data (Geringer and Hebert, 1991;Christoffersen et al, 2014). Lastly, our use of subjective measures is also in line with several recent studies on interfirm collaboration, government support and SME performance (e.g., Ibrahim and Mustapha, 2019;Danso et al, 2016;Neneh, 2018;Thongsri and Chang, 2019;Nakku, et al, 2020). Therefore, taking into account the setting for the study, the SME context and in following past research, this study finds it reasonable to use a subjective measure to capture SME performance.…”
Section: Methodssupporting
confidence: 85%
“…Third, there is evidence for a positive correlation between subjective performance assessments and other objective measures that use accounting or financial data (Geringer and Hebert, 1991;Christoffersen et al, 2014). Lastly, our use of subjective measures is also in line with several recent studies on interfirm collaboration, government support and SME performance (e.g., Ibrahim and Mustapha, 2019;Danso et al, 2016;Neneh, 2018;Thongsri and Chang, 2019;Nakku, et al, 2020). Therefore, taking into account the setting for the study, the SME context and in following past research, this study finds it reasonable to use a subjective measure to capture SME performance.…”
Section: Methodssupporting
confidence: 85%
“…It is crucial for the deepening of international R&D strategies. Firstly, innovation capacity endowment can help enterprises to quickly subdivide overseas markets according to their technical characteristics, production, and product advantages, and find potential markets suitable for their own R&D activities according to strategic objectives [30]. In general, in a macro perspective, market-oriented enterprises tend to favor large-scale countries and regions, while technology-oriented enterprises aim to track and acquire competitors' technology and information, so they usually tend to favor countries and regions with higher levels of expertise to establish international R&D institutions.…”
Section: Innovation Capacity Endowment and International Randd Intensitymentioning
confidence: 99%
“…For market-oriented enterprises, the purpose of international R&D is to collect the information of overseas customers, competitors, and markets, to improve and innovate their technologies based on this information, and to develop products and production processes suitable for the local market, so as to achieve product localization and technology localization [30]. In this process, there are two major challenges.…”
Section: The Mediating Role Of Innovation Capacity Endowmentmentioning
confidence: 99%
“…Organizations that have strong governmental financial and non-financial support can buy new technologies and launch new projects (Caloffiet al, 2015). Several studies have been conducted (Thongsri, & Chang, 2019;Zhang, & Guan, 2018) in which the findings suggested that governmental support such as R & D, grants, and incentives can promote the firm's technological capability. In addition, a lot of organizational support in terms of finance, loans, incentives, and R & D can help the top management in taking confident decisions and investing in risky projects (Brandao-Marques, Correa, & Sapriza, 2020;Uddin, 2016).…”
Section: Government Financial Support and Green Product Innovationmentioning
confidence: 99%